Differences in the epidemiology of theileriosis on smallholder dairy farms in contrasting agro-ecological and grazing strata of highland Kenya - Gitau, G.K.; McDermott, John J.; Katende, J.M.; O'Callaghan, C.J.; Perry, Brian D. (International Society for Veterinary Epidemiology and Economics, 2000)
Tick-borne diseases are considered a major constraint to dairy farming among the smallholder dairy farms in Kenya, which account for an estimated 75-90% of all milk produced in the country. The most important tick-borne disease in Kenya is East Coast fever (ECF) caused by Theileria parva and transmitted by the brown ear tick Rhipicephalus appendiculatus, which has been associated with high mortality in cattle, especially among the exotic breeds of cattle. In Kenya, there is considerable recent evidence that the prevalence of T. parva infections and Reported ECF morbidity, mortality and case-fatality can vary significantly by agro-ecological zone and grazing system. These differences have important implications for both the impact and control of ECF. A paradigm for evaluating production systems for theileriosis based on the epidemiological states i.e. degree of endemic stability or instability has been developed. In endemically stable systems, there is an equilibrium between Theileria parasites and hosts so that ECF impact is minimal despite high infection challenge. In unstable situations, ECF impact can be considerable, either through direct losses from ECF or in costs associated with its control. The prevalence, sero-conversion risk and morbidity/mortality risks of ECF for female calves up to 6 months of age in 5 contrasting agro-ecological zone (AEZ)-grazing system strata in Murang a District, Kenya has been previously described. This paper uses the indicators of theileriosis infection quantified in that study to characterise the epidemiological states of ECF in the 5 AEZ-grazing strata studied in Muranga District, Kenya.